Photosensitive pro-drug nanoassemblies harboring a chemotherapeutic dormancy function potentiates cancer immunotherapy - Jianjun Cheng; Haitian Zhao; Bin Li; Hua Zhang; Qianyu Zhao; Shiyao Fu; Ying Han; Weihong Lu; Jiahua Shi; Xin Yang (Elsevier, 2023)
Immunotherapy combined with effective therapeutics such as chemotherapy and photodynamic therapy have been shown to be a successful strategy to activate anti-tumor immune responses for improved anticancer treatment. However, developing multifunctional biodegradable, biocompatible, low-toxic but highly efficient, and clinically available transformed nano-immunostimulants remains a challenge and is in great demand. Herein, we report and design of a novel carrier-free photo-chemotherapeutic nano-prodrug COS-BA/Ce6 NPs by combining three multifunctional components-a self-assembled natural small molecule betulinic acid (BA), a water-soluble chitosan oligosaccharide (COS), and a low toxic photosensitizer chlorin e6 (Ce6)-to augment the antitumor efficacy of the immune adjuvant anti-PD-L1-mediated cancer immunotherapy. We show that the designed nanodrugs harbored a smart and distinctive "dormancy" characteristic in chemotherapeutic effect with desired lower cytotoxicity, and multiple favorable therapeutic features including improved 1O2 generation induced by the reduced energy gap of Ce6, pH-responsiveness, good biodegradability, and biocompatibility, ensuring a highly efficient, synergistic photochemotherapy. Moreover, when combined with anti-PD-L1 therapy, both nano-coassembly based chemotherapy and chemotherapy/photodynamic therapy (PDT) could effectively activate antitumor immunity when treating primary or distant tumors, opening up potentially attractive possibilities for clinical immunotherapy.